PERANAN ISO 56002 DALAM PENINGKATAN INOVASI ORGANISASI - NURFIDAH NURFIDAH; HARIDA HARIDA; PURNAMAWATI PURNAMAWATI (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2022)
This article aims to review the literature on the role of ISO 56002 in enhancing organizational innovation. The technique used in collecting data is in the form of documenting sources of literature documents. The sources of this literature study are online journal articles and newsletters. Based on the results of the review, it can be concluded that: (1) Standard is a reference used to compare the progress of an organization, while innovation is the application of an idea, technology, service/product, process, new strategy or business model to gain added value for the organization. as well as consumers; (2). Innovation management standards incorporate many elements of innovation so that their main objective, apart from increasing the efficiency or effectiveness of performance practices, is also driven by the need for institutional legitimacy and professional conformity; (3). Implementation of an innovation management system the ISO 56002 standard is able to improve an organization's innovation, and the shortcomings of the ISO 56002 series can be complemented by other ISO 56000 series that are being developed to support the implementation of an innovation management system. ABSTRAKArtikel ini bertujuan mereview literatur tentang peranan ISO 56002 dalam peningkatan inovasi organisasi. Metode penelitian yang digunakan yaitu metode studi literatur, dengan teknik pengumpulan data berupa dokumentasi sumber- sumber dokumen literatur. Sumber dari studi literatur ini berupa artikel jurnal online sebanyak 12 dan newsletter sebanyak 1 yang diterbitkan oleh BNSP. Berdasarkan hasil review dapat disimpulkan bahwa: (1) Standar adalah acuan yang digunakan untuk membandingkan kemajuan suatu organisasi, sedangkan inovasi merupakan penerapan sebuah sebuah, gagasan, teknologi, jasa/produk, proses, strategi baru atau model bisnis untuk mendapatkan nilai tambah baik bagi organisasi maupun konsumennya; (2). Standar manajemen inovasi menggabungkan banyak elemen inovasi sehingga tujuan utamanya selain meningkatkan efisiensi atau efektivitas praktik kinerja, juga didorong oleh kebutuhan akan legitimasi institusional dan kesesuaian profesional; (3). Penerapan Sistem manajemen inovasi Standar ISO 56002 mampu meningkatkan inovasi sebuah organisasi, dan kekurangan yang dimiliki pada seri ISO 56002 dapat dilengkapi dengan seri ISO 56000 lainnya yang sedang dikembangkan untuk mendukung penerapan sistem manajemen inovasi.